HUBUNGAN KELINCAHAN DAN DAYA TAHAN DENGAN HASIL DRIBBLE BOLA BASKET PADA TIM PUTRA SMAN BERNAS PANGKALAN KERINCI - Hotbin Edward Simanjuntak; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to find out whether there is a relationship between agility and endurance with dribble results on the male team of National High School Bernas Pangkalan Kerinci. The form of this study is correlation research, the population in this study is the Team of Men of National High School Bernas Pangkalan Kerinci. The samples in this study were 12 male students from the National High School of Bernas Pangkalan Kerinci. From the calculation of the first analysis Relationships X1 and Y where the rtab at the significant level α (0.05) = 0.602 means rresult (0.688) > rtable (0.602). Means the hypothesis is accepted and there is a significant relationship between agility and dribble results at the National High School Bernas Men Team Pangkalan Kerinci. The second analysis of the relationship between endurance (X2) and dribble results (Y) where rtab at a significant level α (0.05) = 0.602 means rresult (0.630)> rtable (0.602). Means the hypothesis is accepted and there is a meaningful relationship between agility and dribble results on the Men Team of National High School Bernas Pangkalan Kerinci. The third analysis, namely the relationship of agility (X1) and endurance (X2) with dribble results (Y) is significant where rtab at the significant level α (0.05) = 0.602 means rresult (0.724)> rtable (0.602). it means that the hypothesis is accepted and there is a meaningful relationship between agility and endurance with the dribble results in the Team of Men of National High School Bernas Pangkalan Kerinci.Key Words: Agility, Endurance And Dribble Results